(untitled) (Indian Journal of Animal Production and Management, 2014)
The present study was carried out in Surat district of Gujarat to find out the extent of adoption of improved dairy husbandry techniques. A random sample of 300 dairy animal owners were selected and extent of adoption of improved dairy husbandry techniques in six major aspects of housing, feeding, breeding, health care, milking and calf rearing management was studied. Proper orientation of animal shed and housing in separate located place were more adopted in housing techniques. Provide clean and fresh drinking water, feeding balance concentrate mixture on the basis of milk production were more adopted in feeding management. Keeping watch on oestrus cycle and heat symptoms, service/insemination after 12-16 hours since onset of heat and artificial insemination of animals were more adopted by the dairy animal owners. Timely and regularly vaccination and observing animals daily for signs of sickness were more adopted. Hygienic milking and calf rearing techniques were more adopted by the dairy animal owners.